Navigating Modern Parenting Challenges: A Qualitative Study on Islamic Counseling Approaches - Lutfiyatut Tamamiyah (Islamic Counseling and Parenting Journal, 2025)
Parenting in the digital era presents complex challenges that require culturally sensitive approaches, particularly for Muslim families striving to balance religious values with modern realities. This qualitative study explores how Islamic counseling addresses contemporary parenting dilemmas, including digital addiction, moral decline, generational religious gaps, and mental health concerns. Employing a phenomenological design, the research conducted semi-structured interviews and focus group discussions with 15 Muslim parents and 8 Islamic counselors, selected through purposive sampling. Data were analyzed using thematic analysis to identify patterns and solutions grounded in Islamic principles. Findings reveal that Islamic counseling effectively bridges traditional teachings with modern challenges through approaches such as Quranic time management, prophetic storytelling, and integrated spiritual-psychological techniques. Notably, 80% of parents reported behavioral improvements in their children after implementing structured Islamic routines. The study highlights the adaptability of faith-based counseling while emphasizing the need for greater paternal involvement in religious upbringing. These results align with existing literature on Islamic parenting while introducing novel insights, such as parents' preference for brief "micro-counseling" sessions over traditional formats. Practical implications include the development of Islamic digital parenting workshops, father engagement programs, and school-based counseling initiatives. The research contributes to the growing field of Islamic psychology by demonstrating how faith-based approaches can enhance family resilience in multicultural contexts. Future studies should expand to diverse demographics and examine long-term outcomes of these interventions.